Logiczne aspekty języka (naturalnego) - Pietryga, Anna (Investigationes Linguisticae, 2012)
"The paper consists of two parts.Part one presents a number of ambiguities the title of the volume conveys in each of its three Polish lexemes (which are rather similar to the ones used in the English version of the tile). The context of the Birthday leads the author to choose a meaning of the title and accept it as defining the area of further investigation. Part two poses two main questions: 1) does natural language exist in a non – individual way? The answer suggested is it may exist as a result of an (free-will) compromise. Finally, part two addresses metalinguistic questions: a)is formal logic a specialized part of linguistics and b) may one present a methodological evaluation of formal works? Both of these are answered with a tentative yes. "